Hysteroscopically guided transvaginal ultrasound tubal catheterization—a novel office procedure. (September 2016) - Cohen, Shlomo B.; Bouaziz, Jerome; Jakobson-Setton, Ariella; Goldenberg, Motti; Schiff, Eyal; Orvieto, Raoul; Shulman, Adrian
Abstract: Objective: Investigate a novel office hysteroscopic tubal catheterization therapeutic method for proximal tubal occlusion. Study design: Prospective cohort study in a tertiary referral center. We evaluated the procedure on a group of 27 patients that were referred to our unit for proximal tubal occlusion demonstrated by hysterosalpingography, 9 (33.3%) of them with primary infertility and 18 of them (66.6%) with secondary infertility. The intervention included the usage of the modified Novy cornual cannulation set which was inserted through a 5F working cannel during an office operative hysteroscopy, followed by fallopian tube irrigation with saline-air mixture under ultrasonographic imaging. Results: Our series revealed no complication during or after the procedure; anesthesia was not required. One patient lost from follow-up. Of the remaining 26, 10 patients (38.4%) conceived either spontaneously or with treatment by clomiphene or gonadotropine associated with intrauterine insemination. The median time to conception was 5 months (range 4–17). Conclusion: We therefore concluded that office hysteroscopic tubal catheterization is a simple (without anesthesia required) option for the treatment of patients suffering from proximal tubal occlusion. Fertility outcomes in our series are comparable to other treatments options for tubal catheterization. Therefore, tubal catheterization should not delay the assisted reproducted techniques if indicated but we propose to include it in a global integrated approach.